IMPROVING STUDENTS’ SKILLS IN WRITING NARRARTIVE TEXT BY USING DICTOGLOSS DICTATION METHOD - DAYANA, MARGI (Faculty of Tarbiyah nad Teacher Training, 2022)
This research was conducted to find out the improvement of students’ skills in writing narrative text by using the Dictation Dictogloss Method. This research was conducted by implementing the rules and steps of Classroom Action Research. The collected data in this research was analyzed by using qualitative and quantitative technique. The qualitative data was taken from observation sheet, interview, diary notes and documentations. The result of this research found that there was an improvement on students writing narrative skills by applying Dictation Dictogloss Method. It was supported by the increase mean of the score in every single meeting. The mean in pre-test was 40,67. The mean of post-test in cycle one was 65,6. The mean of post-test in cycle two was 70,17. This data indicated that students score was increased in every meeting. The percentage of students passed in every meeting was also improved. The data stated that in pre-test there were only two students passed (6,67%). In the post- test of cycle one there were fourteen students passed (46,67%). In the post-test of cycle two there were twenty students passed (66,67%). By the data gathered in this research, it can be concluded that students were more engaged, motivated and interested in writing narrative text after the implementation of Dictation Dictogloss Method